The Influence Of Leadership And Compensation On Job Satisfaction From A Sharia Management Perspective - Nova Yanti Maleha; Endah Dewi Purnamasari; Havis Aravik (AL-IQTISHADIYAH : EKONOMI SYARIAH DAN HUKUM EKONOMI SYARIAH, 2025)
This study aims to examine the influence of leadership and compensation on employee job satisfaction at PT Jasa Armada Indonesia Tbk, Area IV Palembang, both partially and simultaneously, within the framework of Sharia management. A quantitative approach was employed using a descriptive-associative method, with a saturated sample of all 53 employees. Data were collected through Likert-scale questionnaires and preliminary interviews and analyzed using multiple linear regression with SPSS version 25. The findings indicate that both leadership and compensation have a significant and positive impact on job satisfaction, whether assessed individually or jointly. The coefficient of determination (R² = 0.810) suggests that 81% of the variance in job satisfaction is explained by these two variables, with compensation exerting a stronger influence than leadership. These results are consistent with the Path-Goal Theory, Equity Theory, and Herzberg’s Two-Factor Theory. From the perspective of Sharia management, trustworthy leadership and fair, transparent compensation embody the principles of maqashid sharia, which emphasize justice, employee welfare, and dignity. This study highlights the effectiveness of ethically and spiritually grounded human resource practices in enhancing job satisfaction and fostering organizational well-being.